Analisis Jiwa Kewirausahaan Masyarakat Marind Di Pesisir Pantai Lampu Satu Merauke - Maria Kaok; Putri Inggrid Maria Risamasu (EKONOMI & SOSIAL, 2022)
This study aims to determine the entrepreneurial spirit of the Marind community on the Lampu Satu coast of Merauke. The focus of this research is to measure the level of entrepreneurial spirit possessed by the Marind community, which is the population of this study, the entire Marind community on the coast of Lampu Satu Merauke. This research is a quantitative research with sampling technique using simple random sampling as many as 30 people at random. The method of data collection was carried out by observation, interviews, documentation and questionnaires then after the data was collected it was continued with data analysis using descriptive statistical analysis with validity and reliability tests using SPSS 22. The results of research on 30 respondents showed that r count > r table. The validity test was carried out using SPSS with 22 being declared valid for all questions and the reliability test results were declared reliable because the Cronbach alpha value 0.60 was 0.956. For respondents' level of achievement of 5 indicators above the average of 80%. There is a need for further government intervention in training and socializing the importance of entrepreneurship by seeing the potential possessed by the Marind community to provide change and input for long-term survival to meet their daily economic needs.